Development and characterization of multifunctional carbon fabric‐reinforced polymer composites incorporated with inorganic flame retardants. Issue 8 (29th April 2020) - Afzal, Ayesha; Tariq, Asra; Shakir, Fayzan; Satti, Aamir Naseem; Taimoor, Muhammad; Ghani, Usman; Jaffer, Usman; Rashid, Iqra Abdul; Khaliq, Zubair
Abstract: Carbon fabric‐reinforced polymer (CFRP) composites were incorporated with novel, environment‐friendly and, low‐cost inorganic flame‐retardant (FR) materials. Synergistic properties of potash alum (KA) and magnesium hydroxide (MH) were obtained by infusing these materials in the carbon woven fabric with diglycidial ether of bisphenol‐A epoxy (EP) matrix through resin infusion technology. Composite samples EP80% MH20% and EP80% MH15% KA5% showed Underwriter Laboratories 94 (UL94) V‐2 rating, EP80% MH10% KA10% and EP80% MH5% KA15% showed UL94 V‐1 rating, and EP80% KA20% showed UL94 V‐0 rating. Flame retardancy of EP was improved with increasing concentration of KA up to UL94 V‐0 while a high concentration of MH improved flame retardancy only up to UL94 V‐2 rating, which is not suitable for the material. Flexural modulus and flexural strength of EP were decreased with increasing concentration of KA and MH because both FR created the distance between the EP chains and hence imparted ductility. Thermogravimetric analysis showed an increase in char residue with increasing KA concentration. The char residue of EP100% (without FR materials) was 16.5 wt%, which increased to 71.2 wt% for EP80% KA20% . CFR samples were prepared with the given FR materials and it was seen that reduction in mechanical properties was compensated with the help of CFRP.